The role of energy storage and cross-border interconnections for increasing the flexibility of future power systems : the case of Colombia (2021)
The rapid expansion of renewable energy technologies in the electricity sector introduces new significant challenges for power systems due to their high intermittency. Therefore, more flexibility is needed to ensure that the system can operate reliably and cost-effectively with large shares of variable renewable energy sources (RES). Electricity energy storage and cross-border interconnections are considered two key components for allowing further integration of these sources. Therefore, the aim of this study is to analyse the techno-economic effects of grid-scale electricity storage and interconnections in the integration of variable RES by using the power system of Colombia as a case study. The EnergyPLAN tool was used for building the reference system model and future scenarios. Initially, the technical impacts of electricity storage and interconnections in the power system were examined. Successively, a multi-objective evolutionary algorithm (MOEA) was applied to perform a techno-economic optimisation and identify a set of optimal configurations. The results evidenced that increasing levels of storage and interconnections could allow further penetration of variable RES, achieving total annual electricity production levels of approximately 96.8%. Further, significant reductions in both the fuel consumption and CO2 emissions might permit an emission factor of the power sector of approximately 26.5 gCO2e/kWh